Clinical characteristics and outcomes of COVID-19 cases admitted to adult intensive care units during the pandemic: A single center experience - Majid M. Alshamrani; Aiman El-Saed; Abdulrahman Alalmai; Mohammed Abdulrahman Almanna; Saad Mohammed Dhafer Alqahtani; Mohammed Saad Asiri; Sulaiman Saleh Almasoud; Fatmah Othman (Elsevier, 2024)
Background: COVID-19 is the largest recorded pandemic in history. It causes several complications such as shock, pneumonia, acute respiratory distress syndrome, and organ failure. The objective was to determine COVID-19 outcomes and risk factors in the intensive care (ICU) setting. Methods: A retrospective review of prospectively collected data was conducted. Adult patients with a positive RT-PCR test for COVID-19 admitted to ICUs of a tertiary care hospital between 2020 and 2022 were included. Patients who had severe complex trauma were excluded. The outcomes examined included ventilation use and duration, length of stay (LOS), and mortality. Results: A total of 964 patients were included. The mean ( ± standard deviation, SD) age was 63.7 ± 16.9 years. The majority of the patients were males (59.0 %) and Saudi (75.7 %). Ventilation use was documented in 443 (57.1 %) patients, with a mean ( ± SD) ventilation duration of 9.7 ± 8.4 days. Death occurred in 361 (37.4 %) patients after a mean ( ± SD) of 33.3 ± 44.5 days from infection. The mean ( ± SD) LOS was 30.6 ± 54.1 days in hospital and 5.2 ± 5.4 days in ICU. Ventilation use was associated with older age, males, longer ICU LOS, mortality, and admission to medical-surgical ICU. Crude mortality use was associated with older age, longer ICU LOS, use of ventilator, shorter ventilation duration, and admission to medical-surgical or respiratory ICUs. Conclusions: COVID-19 patients admitted to adult ICUs are at high risk of death and mechanical ventilation. The crude risks of both outcomes are higher in older age and longer ICU LOS and are very variable by ICU type.